Pendampingan Publikasi Karya Ilmiah Bagi Guru SDN 5 Karangbener Kecamatan Bae, Kudus - Fina Fakhriyah; Savitri Wanabuliandari; Sekar Dwi Ardianti (Universitas Mathla'ul Anwar Banten, 2018)
ASSISTANCE OF SCIENTIFIC WRITING PUBLICATION FOR TEACHERS IN SDN 5 KARANGBENER OF BAE SUBDISTRICT, KUDUS. Based on observations in one elementary school in SDN 5 Karangbener, Bae subdistric, Kudus found that for the last 5 years teachers in elementary school have not done publication of scientific papers. Teacher assumes that in compiling scientific papers and publishing them is difficult. In addition, the lack of creative ideas and innovation of teachers in preparing scientific work is also one of the things complained by some teachers in SDN 5 Karangbener. This is because the lack of information for teachers in the preparation of scientific papers and publications of scientific papers. With the accompaniment of the publication of this scientific work will help teachers develop their ability in preparing scientific work and to publish the findings of teachers as implementers of the government education system widely. This mentoring activity is expected to create scientific tradition and culture for teachers through the preparation of scientific works and publications of teachers' scientific works.